Tindak Tutur Joko Anwar yang Mengancam dan Strategi Kesantunan Tidak Langsung terhadap Livi Zheng dalam Acara Q&A: Belaga “Hollywood” di Metro TV - Erin Nur Aini; Ika Nurhayani; Hamamah Hamamah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to investigate the speech acts used by Joko Anwar who threatened live Zheng and politeness strategies in the Q&A program: BELAGA“HOLLYWOOD”. A descriptive method with document analysis is used in this study. The results of this study are found five forms of speech acts namely assertive, directive, commissive, expressive and declarative threatening Livi Zheng. Assertive speech acts in the form of complaining are more often used by Joko Anwar when threatening the face or self-image of Livi Zheng. To reduce the threat, indirect politeness strategies or off-record strategies are used by Joko Anwar. Speech with sarcastic messages or criticisms is conveyed with indirectly meaning, this politeness strategy is chosen so that communication can still be carried out without breaking the cooperative relationship between the speaker and the speech partner. This study shows that although there are threats in the speech delivered, with the indirect politeness strategy is also used to maintain the face or self-image in public.